(untitled) (Economics and region, 2020)
The article discusses the theoretical and practical aspects of lean manufacturing. The authors present the concept of Japanese management technologies, business management and philosophy, which covers almost all aspects of the economic activities of Japanese enterprises. The authors compare the well-known Japanese management concept and the practice of frugality with domestic traditions and production experience and outlines ways to achieve similar results.